Deuterium trapping and sputtering of tungsten coatings exposed to low-energy deuterium plasma - Tolstolutskaya, G.D.; Kuprin, A.S.; Nikitin, A.V.; Kopanets, I.E.; Voyevodin, V.N.; Kolodiy, I.V.; Vasilenko, R.L.; Ilchenko, A.V. (Вопросы атомной науки и техники, 2020)
Processes of sputtering, surface modification and deuterium retention of tungsten coatings were studied under the influence of low-energy (500 eV) deuterium plasma with fluence (2·10²⁴D+/m²) at room temperature. The method of cathodic arc evaporation was used to deposit W and WN-coatings on stainless steel. Results of erosion studies indicated that the sputtering yields for coatings WN and W are 3.1·10⁻³ and 4.8·10⁻³ at./ion, respectively, and at least two times larger compared to bulk W but almost an order of magnitude smaller compared to ferritic martensitic steels. The total D retentions of W coatings were on the order of 5·10¹⁹D/m² and around one orders of magnitude lower than that of WN. Вивчено процеси розпилення, модифікації поверхні і захоплення дейтерію в вольфрамових покриттях під впливом низькоенергетичної (500 еВ) дейтерієвої плазми з флюенсом (4·10²⁴D+/м²). Метод катоднодугового випаровування використано для осадження W- і WN-покриттів на нержавіючу сталь. Результати ерозійних досліджень показали, що коефіцієнти розпилення покриттів WN і W складають 3.1·10⁻³ і 4.8·10⁻³ ат./іон відповідно і, як мінімум, в два рази більше в порівнянні з масивним W, але майже на порядок величини менше в порівнянні з феритно-мартенситними сталями. Загальна кількість дейтерію, утримуваного в W-покритті, становила близько 5·10¹⁹D/м², що приблизно на один порядок нижче, ніж у WN. Изучены процессы распыления, модификации поверхности и захвата дейтерия в вольфрамовых покрытиях под воздействием низкоэнергетической (500 эВ) дейтериевой плазмы с флюенсом (4·10²⁴D+/м²). Метод катодно-дугового испарения использован для осаждения W- и WN-покрытий на нержавеющую сталь. Результаты эрозионных исследований показали, что коэффициенты распыления покрытий WN и W составляют 3,1·10⁻³ и 4,8·10⁻³ ат./ион соответственно и, как минимум, в два раза больше по сравнению с массивным W, но почти на порядок величины меньше по сравнению с ферритно-мартенситными сталями. Общее количество дейтерия, удерживаемого в W-покрытии, составляло около 5·10¹⁹D/м², что примерно на один порядок ниже, чем у WN.